Mastering anti-money laundering and counter-terrorist financing : a compliance guide for practitioners - Parkman, Tim (Pearson, 2019)
This book offers best practice advice on how to meet anti-money laundering (AML) regulations and will help you put together an effective framework to meet your legal obligations. It includes a comprehensive selection of example documents, checklists and an unrivalled collection of training materials. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.